Gestión del cumplimiento de las obligaciones tributarios de la Casa Comercial Los Gemelos Foyain durante el ejercicio económico 2021. - Vergara Loor, Jennifer Edith (2022)
Complying with our tax obligations means keeping up to date with the payment of taxes before the governing body of the Tax Administration; Being up to date allows every business to ideally manage operations subject to taxes, therefore analyzing the tax compliance of the business house "Los Gemelos Foyain" for fiscal year 2021 is essential because in today's world taxes boost economies through At a global level, however, the Tax administration body has to work hard for collection. The commercial "Los Gemelos Foyain" maintain pending tax obligations in 2021, that is, it is going through a difficult fiscal situation, which has influenced that on several occasions it is subject to financial sanctions for the lack of timely compliance with the State, becoming It is important that this business venture has shortcomings in the implementation of tax procedures and records of the tax administration. In Casa Comercial "Los Gemelos Foyain", the processes that are carried out to deal with financial and economic information are complex, as their accounting records are not kept up to date. This case study made it possible to analyze the tax processes, the weaknesses and key failures that hinder taking decisive measures and addressed tax non-compliance. The organization failed to collect information on all the activities that generate cash flows (income), as well as process the monetary values to project the corresponding substitute declarations, with this, when canceling the tax caused and the amounts of its corresponding fines and interest, it would be counted. with tax compliance and the persistent problems with the Tax Administration would be corrected.